Karst Aquifers - Characterization and Engineering - Stevanović, Zoran (Professional Practice in Earth Sciences,, 2015)
This practical training guidebook makes an important contribution to karst hydrogeology. It presents supporting material for academic courses worldwide that include this and similar topics. It is an excellent sourcebook for students and other attendees of the International Karst School: Characterization and Engineering of Karst Aquifers, which opened in Trebinje, Bosnia & Herzegovina in 2014 and which will be organized every year in early summer. As opposed to more theoretical works, this is a catalog of possible engineering interventions in karst and their implications. Although the majority of readers will be professionals with geology/hydrogeology backgrounds, the language is not purely technical making it accessible to a wider audience. This means that the methodology, case studies and experiences presented will also benefit water managers working in karst environments.